Growth and weight deficiency due to the battered child syndrome during the SARS-CoV-2 pandemic - Adam Boroński; Joanna Smyczyńska; Joanna Kudzin; Ewa Toporowska-Kowalska; Agnieszka Szadkowska (Termedia Publishing House, 2024)
During the SARS-CoV-2 pandemic, most visits to primary care clinics were limited to teleconsultations. A 10-year-old boy was referred to the gastroenterology department for abdominal pain and weight loss with a history of behavioural disturbances and pica reported by the parents. On admission, the child had significant growth and weight deficiency. The patient was initially diagnosed with acute mild pancreatitis. Standard treatment resulted in rapid clinical improvement and weight gain. Next, the diagnosis of short stature was extended. Proper nutrition led to a significant increase in height and weight. The cause of all the child's disorders was chronic malnutrition resulting from the conscious, inappropriate behaviour of the caregivers. Finally, the boy was placed in foster care. Restricting health care only to teleconsultations, which does not allow physical examination of the child and assessment of his relationship with the caregivers, can result in an erroneous assessment of the patient's condition.